Organiser - Koureas, Gabriel (My University, 2026)
Organiser of Symposium to coincide with Klitsa Antoniou's exhibition Horizon's at Collection Gallery, Nicosia. With contributions from Esperia Iliadou-Suppiej and Elena Parpa.